3D-hierarchical MoSe2 nanoarchitecture as a highly efficient electrocatalyst for hydrogen evolution. (5th May 2017) - Zheng, Binjie; Chen, Yuanfu; Qi, Fei; Wang, Xinqiang; Zhang, Wanli; Li, Yanrong; Li, Xuesong
Abstract: Clean hydrogen split from water by hydrogen evolution reaction (HER) is significant for sustainability, environmental emissions, and energy security. So far, it is still a big challenge to develop highly efficient noble metal-free electrocatalysts with comparable HER efficiency to platinum-based catalysts, which are mainly hindered by the intrinsic electrocatalytic property and particularly the reasonable nanostructure design of the electrocatalyst. Here we report a newly-designed three-dimensional hierarchical MoSe2 nanoarchitecture (3D-MoSe2 ) with outstanding HER performance. The 3D-MoSe2 is grown by chemical vapor deposition method with using perylene-3, 4, 9, 10-tetracarboxylic acid tetrapotassium salt as a seeding promoter. The as-grown 3D-MoSe2 nanoarchitecture is highly crystalline and constructed with curly few-layered vertical nanosheets onto the horizontal layer, which has much larger (~12 times) electrochemically active area and much smaller (only 2%) charge transfer resistance compared to conventional horizontal MoSe2 layer. With these advantages, the Tafel slope of 3D-MoSe2 can be as small as 47.3 mV/dev, which is the smallest record ever reported for pure MoSe2, even for pure two-dimensional transition metal dichalcogenides (2D-TMDs) catalysts. Furthermore, when 3D-MoSe2 is grown on the multiwall carbon nanotube film, its Tafel slope can be further reduced down to 32.5 mV/dec, which is close to the theoretical limit (29 mV/dec) of HER, and comparable to platinum-based electrocatalysts, making it promising as a highly efficient electrocatalyst for hydrogen evolution.